2015
DOI: 10.1070/qe2015v045n07abeh015782
|View full text |Cite
|
Sign up to set email alerts
|

Study of the absorption coefficient in layers of a semiconductor laser heterostructure

Abstract: Cooperative software engineering typically involves many actors and resources that cooperate in a complex distributed and heterogeneous world. In the DIPS (Distributed Integrated Process Services) project, a three-dimensional model is used for the definition, enactment and tracing of software development processes, which expresses both structure and evolution of such processes. This paper discusses how an optimal architecture was evaluated to implement the process model in a process support framework. Process-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In a number of our preceding experimental studies [9,10], we suggested a procedure for studying the internal optical loss in a laser at high currents in a wide temperature range. This procedure consisted of using a probe optical light introduced into the waveguide of a sample laser under study through one of mirrors of its cavity, passed along the whole cavity, and was collected upon the egress from the opposite mirror, separated from the self emission of a sample, and registered by a high-speed photodetector.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of our preceding experimental studies [9,10], we suggested a procedure for studying the internal optical loss in a laser at high currents in a wide temperature range. This procedure consisted of using a probe optical light introduced into the waveguide of a sample laser under study through one of mirrors of its cavity, passed along the whole cavity, and was collected upon the egress from the opposite mirror, separated from the self emission of a sample, and registered by a high-speed photodetector.…”
Section: Introductionmentioning
confidence: 99%